2012
DOI: 10.1371/journal.pone.0032508
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Quantitative Electroencephalography Reveals Increased Neurophysiologic Connectivity in Depression

Abstract: Symptoms of Major Depressive Disorder (MDD) are hypothesized to arise from dysfunction in brain networks linking the limbic system and cortical regions. Alterations in brain functional cortical connectivity in resting-state networks have been detected with functional imaging techniques, but neurophysiologic connectivity measures have not been systematically examined. We used weighted network analysis to examine resting state functional connectivity as measured by quantitative electroencephalographic (qEEG) coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
150
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(181 citation statements)
references
References 106 publications
(137 reference statements)
19
150
2
10
Order By: Relevance
“…It may be due to the limited number of individual electrodes or the improper measurement method. For the increased global coherence of the MDD group, some researchers interpreted it as adaptive and compensatory mechanisms aimed to overcome the deficient semantic integration [55]. Our findings further support this adaptive and compensatory mechanism.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It may be due to the limited number of individual electrodes or the improper measurement method. For the increased global coherence of the MDD group, some researchers interpreted it as adaptive and compensatory mechanisms aimed to overcome the deficient semantic integration [55]. Our findings further support this adaptive and compensatory mechanism.…”
Section: Discussionsupporting
confidence: 84%
“…Fingelkurts et al [54] reported the increased synchronization was observed in the EEG alpha and theta bands in the patients with MDD. And an increased topographic EEG coherence in the frontal brain areas in the MDD group in the EEG alpha, beta, and theta bands was reported by Leuchter's team [55]. However, the findings in the previous studies are inconsistent and sometimes even contradictory to each other.…”
Section: Discussionmentioning
confidence: 82%
“…More recent studies used a huge variety of connectivity measures like partial directed coherence, Granger causality, structural synchrony index and phase synchrony index. Some found decreased EEG connectivity in MDD [122,132,133,134] while others report of increased EEG connectivity in MDD, mainly in the alpha band [135,136,137,138]. More studies are needed to disentangle the complex relationship between the different connectivity measures and their physiological interpretation and to estimate the value for treatment prediction.…”
Section: Biomarkersmentioning
confidence: 99%
“…Previous work using electroencephalograms (EEGs) to examine inter-region coherence in depressed versus control patients have yielded complex results, with differences found in the proximity of electrode pairs, their hemisphere, and frequency bands (Fingelkurts et al, 2007;Leuchter et al, 2012). The effects on EEG of treatment with SCG DBS are also complex, although generally appear to make depressed brains appear more similar to nondepressed controls (Broadway et al, 2012;Quraan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%